A Co-infection Model System and the Use of Chimeric Proteins to Study Chlamydia Inclusion Proteins Interaction - Han, Ying; Derré, Isabelle (Frontiers in Cellular and Infection Microbiology, 2017)
Chlamydia trachomatis is an obligate intracellular bacterium associated with trachoma and sexually transmitted diseases. During its intracellular developmental cycle, Chlamydia resides in a membrane bound compartment called the inclusion. A subset of Type III secreted effectors, the inclusion membrane proteins (Inc), are inserted into the inclusion membrane. Inc proteins are strategically positioned to promote inclusion interaction with host factors and organelles, a process required for bacterial replication, but little is known about Inc proteins function or host interacting partners. Moreover, it is unclear whether each Inc protein has a distinct function or if a subset of Inc proteins interacts with one another to perform their function. Here, we used IncD as a model to investigate Inc/Inc interaction in the context of Inc protein expression in C. trachomatis. We developed a co-infection model system to display different tagged Inc proteins on the surface of the same inclusion. We also designed chimeric Inc proteins to delineate domains important for interaction. We showed that IncD can self-interact and that the full-length protein is required for dimerization and/or oligomerization. Altogether our approach can be generalized to any Inc protein and will help to characterize the molecular mechanisms by which Chlamydia Inc proteins interact with themselves and/or host factors, eventually leading to a better understanding of C. trachomatis interaction with the mammalian host.